The use of herbal medicines in the treatment of obesity (Research, Society and Development, 2021)
Phytotherapy has been used for a long time in the treatment of obesity, however there are many uncertainties regarding use, requiring health professionals to have a scientific basis. In accordance with Brazilian legislation, the herbal medicine obtained using exclusively plant raw materials is understood as herbal medicines. It is characterized by knowledge of the efficacy and risks of its use, as well as by the reproducibility and constancy of its quality. Its efficacy and safety are validated through ethnopharmacological surveys of use, technoscientific documentation in publications or phase clinical trials. Thus, it is stated that results achieved in the treatment of obesity are satisfactory, with few studies against it, however, the field of phytotherapy is still very controversial, which requires research on the form of prescription, use, toxicity and efficacy.